An Antenna with an Embedded EBG Structure for Non Invasive Hyperthermia Cancer Treatment - Kasumawati, Bt Lias; Mohd Zulkarnaen, Ahmad Narihan; Norlida, Buniyamin (2015)
This paper describes the development on a microstrip antenna that is built with an electromagnetic band gap (EBG) structure integrated within the antenna. The antenna, termed EBG-microstrip (EBG-M) antenna is purposely built for use in a non-invasive hyperthermia cancer treatment. The EBG-M was built with the aim to improve penetration depth and reduce unwanted hot-spots which may damage surrounding healthy tissues during treatment procedures. In addition, this paper provides an overview of a few salient characteristic of an EBG structure which enables the reduction of the hot-spots. Finally, the results of a simulation using Finite Difference Time Domain (FDTD) that show a few of Specific Absorption Rate (SAR) distribution of the proposed EBGM antenna are provided. These preliminary results indicate that an EBG-M antenna have an ability to offer penetration depth with minimize unwanted hot spots which are not required for noninvasive hyperthermia cancer treatment.